Clinical Supervision and Teacher Teaching Performance: A Mediation Model for Work Motivation in Educational Institutions - Mutmainnah (Innovative Pedagogy and Education Studies, 2026)
This study aims to analyze the influence of clinical supervision on teacher performance by considering work motivation as a mediating variable. The background of this research is based on the importance of teacher professional development in improving the quality of education, where clinical supervision is seen as an effective and humanistic approach. The research was conducted at the State Junior High School in Sampang Regency, East Java, involving 159 teachers as respondents. The research method uses an explanatory research type quantitative approach, with data processing using PLS-SEM through the SmartPLS 4.0 application. The results showed that clinical supervision had a positive and significant effect on teacher performance (β = 0.212; p < 0.05), and had a very significant effect on work motivation (β = 0.581; p < 0.001). In addition, work motivation also had a significant influence on teacher performance (β = 0.614; p < 0.001), and was proven to fully mediate the effect of clinical supervision on teacher performance with a mediating effect value of 0.357 (p < 0.001). These findings show that work motivation is an important key link between coaching through supervision and improving teacher performance. The practical implications of this study emphasize the importance of the role of the principal in carrying out supervision that supports the psychological needs of teachers, in order to create a reflective, collaborative, and sustainable work environment.